Genomic analysis reveals a tight link between transcription factor dynamics and regulatory network architecture - Raja Jothi; S Balaji; Arthur Wuster; Joshua A Grochow; Jörg Gsponer; Teresa M Przytycka; L Aravind; M Madan Babu (Molecular Systems Biology)
Abstract Although several studies have provided important insights into the general principles of biological networks, the link between network organization and the genome‐scale dynamics of the underlying entities (genes, mRNAs, and proteins) and its role in systems behavior remain unclear. Here we show that transcription factor (TF) dynamics and regulatory network organization are tightly linked. By classifying TFs in the yeast regulatory network into three hierarchical layers (top, core, and bottom) and integrating diverse genome‐scale datasets, we find that the TFs have static and dynamic properties that are similar within a layer and different across layers. At the protein level, the top‐layer TFs are relatively abundant, long‐lived, and noisy compared with the core‐ and bottom‐layer TFs. Although variability in expression of top‐layer TFs might confer a selective advantage, as this permits at least some members in a clonal cell population to initiate a response to changing conditions, tight regulation of the core‐ and bottom‐layer TFs may minimize noise propagation and ensure fidelity in regulation. We propose that the interplay between network organization and TF dynamics could permit differential utilization of the same underlying network by distinct members of a clonal cell population.